2016
DOI: 10.1002/cam4.718
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic microRNA signatures derived from The Cancer Genome Atlas for head and neck squamous cell carcinomas

Abstract: Identification of novel prognostic biomarkers typically requires a large dataset which provides sufficient statistical power for discovery research. To this end, we took advantage of the high‐throughput data from The Cancer Genome Atlas (TCGA) to identify a set of prognostic biomarkers in head and neck squamous cell carcinomas (HNSCC) including oropharyngeal squamous cell carcinoma (OPSCC) and other subtypes. In this study, we analyzed miRNA‐seq data obtained from TCGA patients to identify prognostic biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 27 publications
(30 reference statements)
2
63
0
Order By: Relevance
“…This is not to say that these miRNAs are not involved in tumor aggressiveness, but that the difference is not useful diagnostically. Recently, using large datasets, two groups have established prognostic RNA-based classifiers for OSCC using 4 miRNAs and for HNSCC using 6 miRNAs [84, 86]. We note that of the excess of 25 miRNAs reported in earlier studies to be relevant to HNSCC and OSCC prognosis prediction only one, mir-218-5p, is in the newly identified OSCC classifier and one, miR-125b-2, in the new HNSCC classifier.…”
Section: Prognosis Of Oscc Based On Mirnas In Surgically Obtained Tissuementioning
confidence: 86%
See 1 more Smart Citation
“…This is not to say that these miRNAs are not involved in tumor aggressiveness, but that the difference is not useful diagnostically. Recently, using large datasets, two groups have established prognostic RNA-based classifiers for OSCC using 4 miRNAs and for HNSCC using 6 miRNAs [84, 86]. We note that of the excess of 25 miRNAs reported in earlier studies to be relevant to HNSCC and OSCC prognosis prediction only one, mir-218-5p, is in the newly identified OSCC classifier and one, miR-125b-2, in the new HNSCC classifier.…”
Section: Prognosis Of Oscc Based On Mirnas In Surgically Obtained Tissuementioning
confidence: 86%
“…We note that of the excess of 25 miRNAs reported in earlier studies to be relevant to HNSCC and OSCC prognosis prediction only one, mir-218-5p, is in the newly identified OSCC classifier and one, miR-125b-2, in the new HNSCC classifier. Of greater concern is that in the study where the information is provided, the changes in miRNA marker levels between the high risk (short overall survival) versus low risk (long overall survival) are slight, 19% to 43% [86]. Thus usage of the measurement of levels of these markers to predict prognosis would require extreme accuracy in miRNA measurement for usage in the clinic.…”
Section: Prognosis Of Oscc Based On Mirnas In Surgically Obtained Tissuementioning
confidence: 99%
“…12). These two mutual miRNAs (hsamiR-455-5p and hsa-miR-181d-5p) have been repeatedly found to be overexpressed in other malignancies (219)(220)(221). Interestingly, there was no difference in miRNA expression between breast ACC and normal breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several diagnostic and predicted miRNAs signature have revealed by scientists worldwide. It was reported that several miRNAs markers were identified for cancer prediction and prognosis, such as head and neck squamous cell carcinomas7, bile duct cancer prediction8, and glioma9. However, up to date, the miRNAs expression patterns in the survival prognosis of colon cancer have not been investigated systematically.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that several miRNAs markers were identified in caners, such as head and neck squamous cell carcinomas7, six-miRNAs signature in bile duct cancer prediction8, and 5-miRNAs prognosis in glioma9. However, as to the smaller patient number or limited miRNAs number, or different miRNAs-chip platform in colon cancer study, studies lacked a normalized standard.…”
mentioning
confidence: 99%